Effects of Caulis Spatholobi Polysaccharide on Immunity, Intestinal Mucosal Barrier Function, and Intestinal Microbiota in Cyclophosphamide-Induced Immunosuppressive Chickens - Cui, Yao; Sun, Wenjing; Li, Qinmei; Wang, Kaijun; Wang, Yuhan; Lv, Feifei; Chen, Xiaogang; Peng, Xiaomin; Wang, Ying; Li, Jiang; Si, Hongbin (Frontiers in Veterinary Science, 2022)
The protective effect of Caulis Spatholobi Polysaccharide (CSP) on immune function, intestinal mucosal barrier and intestinal microflora in cyclophosphamide (CY) induced immunosuppressed chickens were rarely reported. This study was designed to investigate the cecal microbiota in chickens and aimed to elucidate the immune mechanism involved in the CSP to CY induced immunosuppressed. A total of 288 cocks were equally divided into six groups and used to evaluate the immune effect of CSP on cocks. Results showed that the CSP could increase the body weight and immune organ index of immunosuppressed chickens, significantly increase the secretion of cytokines (IL-4, IL-10) and immunoglobulin (IgG, IgM) in serum of chickens, and restored the immune function of the body. The CSP reduced intestinal injury of jejunum and ileum, increased the ratio of intestinal villus height to crypt depth (V/C), improved the expression of tight junction protein, and protected intestinal health. The CSP activates the TLRs/MyD88/ NF-κB p65 pathway, and enhanced the expression of toll-like receptor 4 (TLR4), MyD88, NF-κB, Cloudin1, ZO-1 protecting the intestinal tract. High-throughput sequencing of the 16S rRNA gene showed that CSP increased species richness, restored CY induced intestinal microbiome imbalance, and enhanced the abundance of Lactobacillus in the intestinal tract. In conclusion, our study provides a scientific basis for CSP as an immune enhancer to regulate intestinal microflora and protect intestinal mucosal damage in chickens.